IN-PATIENT SERVICES SATISFACTION SURVEY IN PNS RAHAT HOSPITAL KARACHI: In–Patient Services Satisfaction Survey - Ahmad, Mobeen; Iqbal, Muhammad Hatif; Haq, Riaz ul (Pakistan Armed Forces Medical Journal, 2015)
Objective: To study the key indicators of satisfaction for admitted patients in PNS Rahat.Study Design: Single Step Cross-Sectional Survey.Place and Duration of Study:  PNS Rahat, June 2007 to Dec 2007.Patients and Methods:   Priority population of 450 admitted patients whose feedback was recorded through a written questionnaire having 15 close ended questions out of which 2 questions were later excogitated to reduce study bias (duplication).Results: Ninety three point seven percent (n%) patients filled the questionnaire reducing the sample size to 422 out of 450 patient approached. Fifty six point three percent patients were highly satisfied, 29.1% patients were moderately satisfied, 11.56% patients were just satisfied and 2.7%remained unsatisfied with hospital services provided during admission. In highly satisfied patients, performance of consultants was rated 82.7%. In moderately satisfied patients, standard of catering in ward was rated 41.5 %. Twenty nine point five percent patients remained just satisfied and 25.4% were unsatisfied with hospital canteen services.Conclusion: Winning hearts and minds of admitted patients relies on consultants’ and nurses’ competence and availability. However, patients are highly dissatisfied by substandard catering in wards, unhygienic conditions and insufficient hospital canteen services.